2020
DOI: 10.1101/2020.01.08.899153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Short-term changes in polysaccharide utilization mechanisms of marine bacterioplankton during a spring phytoplankton bloom

Abstract: SummarySpring phytoplankton blooms in temperate environments contribute disproportionately to global marine productivity. Bloom-derived organic matter, much of it occurring as polysaccharides, fuels biogeochemical cycles driven by interacting autotrophic and heterotrophic communities. We tracked changes in the mode of polysaccharide utilization by heterotrophic bacteria during the course of a diatom-dominated bloom in the German Bight, North Sea. Polysaccharides can be taken up in a ‘selfish’ mode, where initi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 44 publications
3
17
0
Order By: Relevance
“…The synthesis of these findings generally agrees with previous observations that Bacteroidetes populations increase in relative abundance and cell-specific activity in the middle and late phases of phytoplankton blooms and encode a large number of specialized enzymes allowing for the degradation and assimilation of polysaccharides ( 17 , 26 , 53 , 55 58 ). Our data further suggest that lysate DOM, particularly those derived from diatoms, stimulate higher cellular growth rates in Bacteroidetes taxa relative to other co-occurring populations and other substrates we tested, allowing this lineage to translate their resource use strategy into growth and division in a suitable environment.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The synthesis of these findings generally agrees with previous observations that Bacteroidetes populations increase in relative abundance and cell-specific activity in the middle and late phases of phytoplankton blooms and encode a large number of specialized enzymes allowing for the degradation and assimilation of polysaccharides ( 17 , 26 , 53 , 55 58 ). Our data further suggest that lysate DOM, particularly those derived from diatoms, stimulate higher cellular growth rates in Bacteroidetes taxa relative to other co-occurring populations and other substrates we tested, allowing this lineage to translate their resource use strategy into growth and division in a suitable environment.…”
Section: Discussionsupporting
confidence: 91%
“…Both peroxiredoxin enzymes and biopolymer transporters assigned to the Bacteroidetes became enriched in all substrate treatments, except for the cyanobacteria exudate treatment, implying that cells of this lineage are particularly well-suited for growth in the phycosphere, where oxygen levels and mucilage will be highest. The synthesis of these findings generally agrees with previous observations that Bacteroidetes populations increase in relative abundance and cell-specific activity in the middle and late phases of phytoplankton blooms and encode a large number of specialized enzymes allowing for the degradation and assimilation of polysaccharides (17,26,53,(55)(56)(57)(58). Our data further suggest that lysate DOM, particularly those derived from diatoms, stimulate higher cellular growth rates in Bacteroidetes taxa relative to other co-occurring populations and other substrates we tested, allowing this lineage to translate their resource use strategy into growth and division in a suitable environment.…”
Section: Protein Expression and Ecophysiological Evidence For Bacteroidetessupporting
confidence: 90%
“…1, data previously published in ref. [71]), implying a longer bloom than has been observed in prior years [5]. The composition of the algal community was similar to prior years [5], being dominated by diatoms (Supplementary Fig.…”
Section: Helgoland Phytoplankton Bloommentioning
confidence: 62%
“…This event would increase the richness of the community and, potentially, result in the generation of additional secondary metabolites that benefit the lifestyle of MGs. Furthermore, it has been shown that both the concentrations and complexity of available substrate cause differential selection of distributive or selfish foraging strategies [47][48][49].…”
Section: Discussionmentioning
confidence: 99%